THE IMPLEMENTATION OF LANGUAGE POLICY IN STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA - Afifah Nurul Khoirot (Buletin Al-Turas, 2017)
This study is aimed to analyze language policy in State Islamic University of North Sumatera. The researcher studied language policy in State Islamic University of North Sumatera. This study was conducted by using qualitative research, This study was conducted as a case study. The research described the implementation of languae policy which occur in State Islamic University of North Sumatera. And also explained the reason why the language policy is needed in State Islamic University of North Sumatera. Data in this study were taken from the documentation of official act about Peraturan Menteri Agama Nomor 10 Tahun 2016 in Paragraph 4 Bahasa Pengantar Pasal 16. Another data was taken from result of observation of the lecturer communication in classroom. There are three lecturers who have observed from different major. In doing this research, there are some steps used by the researcher in collecting the data. First, recorded the language used The second, the researcher analyzed the language recorded. The result of this study were Language policy well implemented in State Islamic University of North Sumatera, the use of foreign language is also found and it’s not dominant. Bahasa Indonesia still used dominantly in this university and State Islamic University of North Sumatera used Bahasa Indonesia as their lingua franca between lecturer and students in the classroom interaction.DOI : 10.15408/bat.v23i2.5671